The European Travel Information and Authorization System (ETIAS): Enhancing Counterterrorism and Counterintelligence Efforts - Kanellopoulos, Anastasios Nikolaos (HAPSc Policy Briefs Series, 2023)
The European Travel Information and Authorization System (ETIAS) is set to revolutionize border security in the European Union. Scheduled for operation in 2025, it will screen travelers from visa-exempt countries, enhancing security by identifying potential threats such as terrorism, organized crime, and illegal migration. Regulated by EU legislation and involving a detailed application process, the system collects and cross-references traveler data with various databases to assess security, public health, and migration risks. While ETIAS is a powerful tool for counterterrorism, preventing entry of potential terrorists, it is also an advanced counterintelligence asset, employing intelligence capabilities to detect espionage and Intelligence related activities and act as a deterrent to potential spies. With a comprehensive approach, the present paper describes the ETIAS promises to bolster EU security.